The relationships between morphological characteristics and foraging behavior in four selected species of shorebirds and water birds utilizing tropical mudflats - Norazlimi, Nor Atiqah; Ramli, Rosli (Hindawi Publishing Corporation, 2015)
A study was conducted to investigate the relationship between the physical morphology of shorebirds and water birds (i.e., Lesser adjutant (Leptoptilos javanicus), Common redshank (Tringa totanus),Whimbrel (Numenius phaeopus), and Little heron (Butorides striata)) and their foraging behavior in the mudflats area of Selangor, Peninsular Malaysia, from August 2013 to July 2014 by using direct observation techniques (using binoculars and a video recorder).The actively foraging bird species were watched, and their foraging activities were recorded for at least 30 seconds for up to a maximum of five minutes. A Spearman Rank Correlation highlighted a significant relationship between bill size and foraging time (